Use of Cyclosporine A and danazol in treatment of aplastic anemia: A real-world data from a teaching hospital in South India - Kamat, Girish; Renukaradhya K Math; Goni, Deepak; Balikai, Girish; Savanur, Ambuja; Mudennavar, Nayana; Palaksha Kanive Javaregowda (Asian Journal of Medical Sciences, 2022)
Background: Due to financial constraints, there are limited treatment options for Aplastic anemia (AA) in developing countries. Aims and Objectives: In the present observational retrospective study, utility of Cyclosporine A (CsA) along with Danazol (an anabolic steroid) in AA was assessed. Materials and Methods: The study included patients of AA treated in our hospital from 2017 to 2020. Results: The present study included total of 95 patients. Out of these, 69 patients (73%) were lost to follow-up. It was observed that, out of 26 patients who could be followed up, 18 (69%) patients responded to the treatment (transfusion independent) at the end of 6 months. Out of 18 patients who had responded, two were very severe AA, 12 were severe AA, and four were non-severe AA patients. Eleven out of 18 (61.1%) females responded, whereas seven out of eight males (87.5%) responded to the treatment. In four patients who received Eltrombopag in addition to CsA-Danazol, three patients responded to the therapy. Conclusion: Treatment with CsA and Danazol may represent a promising therapy for patients with AA, especially in resource limited settings. Further, large-scale collaborative studies are necessary to evaluate such approaches in management of AA.